Geistesgeschichte en Christelike Wetenskap . Betogings vir en teen ’n Christelike siening van kunsgeskiedenis* - Snyman, Johan (Koers, 1981)
This essay has three motives. In the first place it wants to argue against Wellek and Warren who maintain that all extrinsic approaches to art are unable to furnish aesthetics with a “rational” foundation. But if Wellek and Warren's claim is a crass generalization, it does not mean that a so called Christian approach to art can easily be justified. Therefore, secondly, a critique - a Christian scientific critique - of some current and so called Christian views on art has become necessary. The last motive, a somewhat old-fashioned one, seems to contravene the second one: this essay wants to state a case for a Christian approach to (the history of) art.